miRNA-200b—A Potential Biomarker Identified in a Porcine Model of Cardiogenic Shock and Mechanical Unloading - Riehle, Christian; Sieweke, Jan-Thorben; Bakshi, Sayan; Ha, Chae-Myeong; Junker Udesen, Nanna Louise; Møller-Helgestad, Ole K.; Froese, Natali; Berg Ravn, Hanne; Bähre, Heike; Geffers, Robert; Seifert, Roland; Møller, Jacob E.; et al. (Frontiers in Cardiovascular Medicine, 2022)
Background: Cardiogenic shock (CS) alters whole body metabolism and circulating biomarkers serve as prognostic markers in CS patients. Percutaneous ventricular assist devices (pVADs) unload the left ventricle by actively ejecting blood into the aorta. The goal of the present study was to identify alterations in circulating metabolites and transcripts in a large animal model that might serve as potential prognostic biomarkers in acute CS and additional left ventricular unloading by Impella® pVAD support. Methods: CS was induced in a preclinical large animal model by injecting microspheres into the left coronary artery system in six pigs. After the induction of CS, mechanical pVAD support was implemented for 30 minutes total. Serum samples were collected under basal conditions, after the onset of CS, and following additional pVAD unloading. Circulating metabolites were determined by metabolomic analysis, circulating RNA entities by RNA sequencing. Results: CS and additional pVAD support alter the abundance of circulating metabolites involved in Aminoacyl-tRNA biosynthesis and amino acid metabolism. RNA sequencing revealed decreased abundance of the hypoxia sensitive miRNA-200b following the induction of CS, which was reversed following pVAD support. Conclusions: The hypoxamir miRNA-200b is a potential circulating marker that is repressed in CS and is restored following pVAD support. The early transcriptional response with increased miRNA-200b expression following only 30 minutes of pVAD support suggests that mechanical unloading alters whole body metabolism. Future studies are required to delineate the impact of serum miRNA-200b levels as a prognostic marker in patients with acute CS and pVAD unloading.